Constitutive Overexpression of the Plasma Membrane Na+/H+ Antiporter for Conferring Salinity Tolerance in Rice (Plant Tissue Culture and Biotechnology, 2016)
At the cellular level, the Salt Overly Sensitive (SOS) signaling pathway comprising SOS3, SOS2, and SOS1 has been proposed to mediate cellular signaling under salt stress to maintain ion (Na+) homeostasis. In this regulatory pathway, both OsSOS1 encoding plasma membrane and OsNHX1 encoding vacuolar Na+/H+ antiporters are regulated by SOS3?SOS2 protein kinase complex. In the present study, the rice variety BRRI dhan28 - which is popular with farmers and high yielding, but salt sensitive, was transformed with the OsSOS1 gene isolated from salt tolerant Pokkali rice and driven by the constitutive promoter, CaMV35S. The construct was transformed through a tissue culture-independent Agrobacteriummediated in planta transformation method that circumvents the problems associated with tissue culture-based indica rice transformation methods. Integration of the foreign genes (OsSOS1) into the genome of transgenic plants was confirmed by gene-specific PCR and Southern blot analysis. The level of transgene expression (SOS1) was also quantified by semi-quantitative RT PCR and real time PCR. Genetic segregation ratio for T1 progenies was calculated and found to follow the Mendelian law of inheritance in case of positive transformants. The transformants were shown to be salt tolerant compared to wild type in molecular analysis as well as physiological screening. Future work will involve transformation of both the OsSOS1 and OsNHX1 genes together; with the expectation for enhancing the tolerance level compared to currently available transgenic rice.Plant Tissue Cult. & Biotech. 25(2): 257-272, 2015 (December)